Predisposing Factors Associated with Health Behavior in Deli Serdang, North Sumatera - Pomarida Simbolon; Connie Melva Sianipar (Journal of Health Promotion and Behavior, 2018)
Background: Clean and healthy life behavior (PHBS) is expected to reduce the risk of disease and improve the quality of health. PHBS in order school is an attempt to empower students, teachers and the public school environment in order to know, willing, and able to practice healthy hygiene practices. This study aimed to analyze the relationship of predisposing factors associated with PHBS in Deli Serdang.Subjects and Method: This study was a cross-sectional study conducted at Pancur Batu Senior High School, Deli Serdang, Medan, from April to May 2018. A sample of 88 students was selected for this study by simple random sampling. The dependent variable was PHBS. The independent variables were teacher's knowledge, attitude, and support. The data were collected using a questionnaire and analyzed by Chi square test.Result: Positive attitude (OR= 7.88; 95% CI= 2.94 to 21.11; p= 0.001), high knowledge (OR= 7.88; 95% CI= 2.94 to 21.11; p= 0.001), and strong support (OR= 16.88; 95% CI = 4.33 to 65.71; p = 0.001) improved PHBS.Conclusion: Positive attitude (OR= 7.88; 95% CI= 2.94 to 21.11; p= 0.001), high knowledge (OR= 7.88; 95% CI= 2.94 to 21.11; p= 0.001), and strong support (OR= 16.88; 95% CI = 4.33 to 65.71; p = 0.001) improved PHBS.Keywords: knowledge, attitude, teacher support, clean and healthy life behaviorCorrespondence: Pomarida Simbolon. STIKes Santa Elisabeth, Medan, Sumatera Utara. Jl. Bunga Terompet No.118, Sempakata, Medan Selayang, Kota Medan 20131, Sumatera Utara. Email: pomasps@yahoo.com. Mobile: 085361806500.Health Promotion and Behavior (2018), 3(2): 130-138https://doi.org/10.26911/thejhpb.2018.03.02.07